Implementation of CRM (Customer Relationship Management) Using Zoho CRM (Case Study: Villa Gangga) - Krisnawan, I Made Dwi; Githa, Dwi Putra; Wiranatha, Anak Agung Ketut Agung Cahyawan (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 5 No 1 (2024): JITTER, Vol.5, No.1, April 2024, 2024)
The main objective of initiating a business is to achieve maximum profit. To attain this goal, a company must be capable of utilizing existing technology to compete and cultivate a loyal customer base. Villa Gangga is a family-oriented accommodation business located in the Ababi Village, Abang District, Karangasem Regency, Bali. The business has been running for 15 years, relying on a conventional CRM system that only uses manual record-keeping and workflow design. However, this system is susceptible to human errors and other issues. Therefore, in this study, Customer Relationship Management (CRM) implementation was carried out using the Low Code development platform named Zoho Creator to enhance customer satisfaction by improving the relationship between buyers and sellers and addressing customer complaints. The research results indicate that the CRM implementation at Villa Gangga has enhanced business performance. Consequently, the implementation of CRM using Zoho Creator at Villa Gangga is highly recommended for entrepreneurs in the tourism industry seeking to enhance service quality and customer satisfaction.